A Pilot Study of the Safety and Initial Efficacy of Ivermectin for the Treatment of Alcohol Use Disorder. (18th April 2016) - Roche, Daniel J. O.; Yardley, Megan M.; Lunny, Katy F.; Louie, Stan G.; Davies, Daryl L.; Miotto, Karen; Ray, Lara A.
Abstract : Background: Ivermectin (IVM) is an antiparasitic agent that has been shown to reduce alcohol intake in mice, suggesting IVM as a potential treatment for alcohol use disorder (AUD). However, the safety profile of IVM administered in combination with an intoxicating dose of alcohol has not been characterized in humans. Methods: This pilot project sought to provide the first clinical evidence that IVM could be repositioned as an AUD pharmacotherapy by examining (i) the safety of combining IVM (30 mg oral, once a day [QD]) with an intoxicating dose of intravenous alcohol (0.08 g/dl) and (ii) the effects of IVM on alcohol cue‐induced craving and subjective response to alcohol. Eleven individuals with AUD participated in a randomized, placebo‐controlled, crossover study in which they received the study medication, participated in a cue exposure paradigm followed by intravenous alcohol administration, and remained in an inpatient unit overnight for observation. Results: IVM treatment, versus placebo, did not increase the number or severity of adverse effects during alcohol administration or throughout the visit. However, IVM did not reduce cue‐induced craving nor did it significantly affect subjective response to alcohol. Conclusions: These results suggest that IVM (30 mg oral, QD) is safe in combination with an intoxicating dose of alcohol, but do not provide evidence that this dose of IVM is effective in reducing alcohol craving or its reinforcing effects. Given the preclinical data suggesting IVM is effective in reducing alcohol consumption in mice, additional studies testing larger samples and alternate dosing regimens are warranted to further characterize the potential efficacy of IVM as an AUD treatment. Abstract : Ivermectin (30 mg) did not increase the number or severity of adverse effects during alcohol administration. However, ivermectin also did not affect cue‐induced craving and subjective response to alcohol. These pilot results suggest that ivermectin is safe in combination with an intoxicating dose of alcohol, but do not indicate that this dose of ivermectin produces anti‐alcohol effects in humans. Additional studies testing larger samples and alternate dosing regimens are needed to test the potential efficacy of ivermectin as an alcoholism treatment.